Factors influencing consumption decision of fresh fruits from Malaysia: a case of foreign nationals in Malaysia - Suntharalingam, Chubashini; Terano, Rika (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2017)
This study was carried out as a move to increase Malaysia’s fruit exports. The purpose of this study was to identify factors that influence the consumption decision of foreign nationals in Malaysia as move to understand their behavior and pattern in purchasing fresh fruits from Malaysia. This study was carried out in Malaysia among foreign nationals and it was found to be the first of its nature to be carried out in Malaysia. A total of eighty three respondents participated in six focus group discussions. Data was analyzed via exploratory factor analysis which is commonly used in examining consumer preferences and behavior. The three factors identified in influencing the consumption decision of Malaysian fresh fruits among foreign nationals were (1) price and fruit intrinsic attributes; (2) fruit physical aspects and uniqueness; and (3) occasion, familiarity and user status.